1946
DOI: 10.1021/jo01174a012
|View full text |Cite
|
Sign up to set email alerts
|

THE SYNTHESIS OF POTENTIAL ANTIMALARIALS. SOME SUBSTITUTED N-PHENYLSULFONAMIDES1

Abstract: Drugs of the sulfonamide type have recently been extensively investigated as antimalarials. As part of this general program the compounds in Table I were prepared.3As intermediates, several unreported aniline derivatives were required and their preparation is also described.These compounds were prepared by coupling an appropriate sulfonyl chloride with the required aniline derivative and hydrolyzing or reducing the product to the final compound. The method of coupling and hydrolysis employed was essentially th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…163~166 ℃ (lit. [12] 163~166 2962,2889,2853,1593,1565,1481,1436,1376,1312,1243,1160,1121,1070 (KBr) v: 3088, 3060, 2912(KBr) v: 3088, 3060, , 2854(KBr) v: 3088, 3060, , 1623(KBr) v: 3088, 3060, , 1572(KBr) v: 3088, 3060, , 1523(KBr) v: 3088, 3060, , 1481(KBr) v: 3088, 3060, , 1446(KBr) v: 3088, 3060, , 1342(KBr) v: 3088, 3060, , 1224(KBr) v: 3088, 3060, , 1190 2-吗啡啉基苯并噻唑(3l) [20] : 1 H NMR (400 MHz, DMSO-d 6 ) δ: 7.42~7.40 (m, 1H), 7.31~7.29 (m, 1H), 7.18~7.14 (m, 1H), 7.05~7.01 (m, 1H), 3.73~3.70 (m, 4H), 3.59~3.57 (m, 4H); 13 C NMR (100 MHz, CDCl 3 ) δ: 168. 9, 152.4, 130.5, 126.0, 121.6, 120.7, 119.2, 77.3, 77.0, 76.7, 66.2, 48.4; MS (ESI) m/z (%): 221.1 (M + , 100).…”
Section: 一锅分步氨化反应mentioning
confidence: 99%
“…163~166 ℃ (lit. [12] 163~166 2962,2889,2853,1593,1565,1481,1436,1376,1312,1243,1160,1121,1070 (KBr) v: 3088, 3060, 2912(KBr) v: 3088, 3060, , 2854(KBr) v: 3088, 3060, , 1623(KBr) v: 3088, 3060, , 1572(KBr) v: 3088, 3060, , 1523(KBr) v: 3088, 3060, , 1481(KBr) v: 3088, 3060, , 1446(KBr) v: 3088, 3060, , 1342(KBr) v: 3088, 3060, , 1224(KBr) v: 3088, 3060, , 1190 2-吗啡啉基苯并噻唑(3l) [20] : 1 H NMR (400 MHz, DMSO-d 6 ) δ: 7.42~7.40 (m, 1H), 7.31~7.29 (m, 1H), 7.18~7.14 (m, 1H), 7.05~7.01 (m, 1H), 3.73~3.70 (m, 4H), 3.59~3.57 (m, 4H); 13 C NMR (100 MHz, CDCl 3 ) δ: 168. 9, 152.4, 130.5, 126.0, 121.6, 120.7, 119.2, 77.3, 77.0, 76.7, 66.2, 48.4; MS (ESI) m/z (%): 221.1 (M + , 100).…”
Section: 一锅分步氨化反应mentioning
confidence: 99%
“…For the preparation of compounds (III) and (IV), 3,5-dibromo-4iodonitrobenzene, (I), was prepared from 2,6-dibromo-4-nitroaniline, (II) (Senear et al, 1946). (I) (1.50 g, 3.69 mmol), CuCl (54.5 mg, 0.55 mmol) and [Pd(PPh 3 ) 2 Cl 2 ] (381 mg, 0.54 mmol) were dissolved in Et 3 N (50 ml) under argon.…”
Section: Methodsmentioning
confidence: 99%
“…During these studies, we have developed routes to a number of alkyne-containing building blocks containing mixed halo substituents to facilitate preferential alkyne-coupling at specific sites under Sonogashira conditions (Sonogashira et al, 1975;Sonogashira, 2002). A key building block is (I) (see scheme), which is prepared from 2,6-dibromo-4-nitroaniline, (II) (Senear et al 1946). In the reaction of a crude sample of (I) containing (II) with i Pr 3 SiCCH under Sonogashira conditions, we isolated a single crystal of (IV) in addition to the expected alkyne (III).…”
Section: Commentmentioning
confidence: 99%
“…DBNMNA (m.p. 389-390 K) was prepared by the reaction of bromine with N,N-dimethyl-4-nitroaniline in methanol at reflux (Tsuda, 1969;* Senear, Rapport, Mead, Maynard & Koepfli, 1946;Blanksma, 1902). Powder X-ray diffraction patterns, obtained using a Philips APD-3600 diffractometer in parafocus geometry using Cu Ka radiation, showed that crystals obtained from acetonitrile, ethanol and methylene chloride all have the same structure.…”
mentioning
confidence: 99%